1991
DOI: 10.2307/30146996
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Response to Intramuscular Versus Low Dose Intradermal Hepatitis B Booster Immunization

Abstract: Plasma-derived hepatitis B vaccine recipients with anti-HBs levels greater than or equal to 10 mIU/mL at 24 to 36 months after primary immunization are likely to maintain these levels two years later. The diminished durability of the antibody response together with the increased rate of local side effects associated with the ID injection route may limit its applicability as an alternative to using IM booster doses of hepatitis B vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that antibody is usually undetectable in approximately 40% of recipients within 4 years of vaccination. 14 " 16 West et al 17 showed that the proportion of seropositive persons at 2 years following vaccination was a function of the level of the initial response. Our study suggests that initial HBsAb titer does not predict (17) Abbreviations: GMT, geometric mean titers; HBsAb, hepatitis B surface antibody; ID, intradermal; IM, intramuscular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that antibody is usually undetectable in approximately 40% of recipients within 4 years of vaccination. 14 " 16 West et al 17 showed that the proportion of seropositive persons at 2 years following vaccination was a function of the level of the initial response. Our study suggests that initial HBsAb titer does not predict (17) Abbreviations: GMT, geometric mean titers; HBsAb, hepatitis B surface antibody; ID, intradermal; IM, intramuscular.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a number of studies support the hypothesis that continued protection against infection may not be dependent on persistence of detectable antibody 1417 " 20 and that a single booster injection produces a clear anamnestic response in at least 90% of vac-cines within 2 to 4 weeks. 16,21 McKinney et al 16 found that a one-dose IM or ID booster injection produced seropositivity (3=10 IU/mL) in 100% of subjects and that 64% of the ID group (14/22) and 89% of the IM group (17/19) remained seropositive after 27 months. These studies support the hypothesis that vaccine recipients maintain an immunologic memory against hepatitis antigens and can mount an anamnestic response to subsequent viral exposure.…”
Section: Discussionmentioning
confidence: 99%